Pripovedi iz izgnančinega fotoalbuma - Simikič, Alenka (Etnolog. Nova vrsta (Ljubljana), 2002)
Using photographs from the album of Terezija Barkovič, née Novoselič, the article presents the memories of the 1941-1945 war years of three of her sisters and abrother The Novoselič family, consisting of father, mother, and eleven children lived in Nova vas near Mokrice and was exiled on November 1, 1941. They spent the first months of their exile in the Münchenberg, Templin, and Leutesdorf camps' towards the end of 1942 the entire family was sent to the property of the winegrower Adolf Schmidt in Nierstein on the Rhine, where they remained until the liberation.
Keywords: fotografije; spomini; biografije; izgnanci; druga svetovna vojna; World War II; zgodovinski pregledi; Slovenia; Slovenija